2019
DOI: 10.1038/s41593-018-0300-4
|View full text |Cite
|
Sign up to set email alerts
|

ALS-implicated protein TDP-43 sustains levels of STMN2, a mediator of motor neuron growth and repair

Abstract: Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, subject always to the full Conditions of use:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
583
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 434 publications
(685 citation statements)
references
References 64 publications
35
583
1
2
Order By: Relevance
“…Similarly, examination of downregulated genes overlapping among the Blue and Midnightblue modules in data set A, the Darkgreen module in data set B, and MNs highlighted genes previously implicated in ALS (Lederer et al, 2007;Saris et al, 2009;Umahara et al, 2016) ( Figure 5D). The GO term regulation of neuronal projection development was significantly represented among the overlapping, downregulated genes ( Figure 5D), consistent with recent models suggesting that deficiencies in maintaining axonal projections may underlie ALS (Klim et al, 2019;Melamed et al, 2019).…”
Section: Als Ipsc-mn Cultures Exhibit Transcriptional Changes Detectasupporting
confidence: 88%
See 3 more Smart Citations
“…Similarly, examination of downregulated genes overlapping among the Blue and Midnightblue modules in data set A, the Darkgreen module in data set B, and MNs highlighted genes previously implicated in ALS (Lederer et al, 2007;Saris et al, 2009;Umahara et al, 2016) ( Figure 5D). The GO term regulation of neuronal projection development was significantly represented among the overlapping, downregulated genes ( Figure 5D), consistent with recent models suggesting that deficiencies in maintaining axonal projections may underlie ALS (Klim et al, 2019;Melamed et al, 2019).…”
Section: Als Ipsc-mn Cultures Exhibit Transcriptional Changes Detectasupporting
confidence: 88%
“…The most recent iPSC-based transcriptomic reports performed RNA profiling at time points during differentiation concomitant with various observed ALS phenotypes which include nuclear RNA foci (Sareen et al, 2013), decreased neurite length (Fujimori et al, 2018), reduced neurite repair after injury (Klim et al, 2019;Melamed et al, 2019), and MN death (Kiskinis et al, 2014;Shi et al, 2018). Several of these protocols differentiated iPSCs for over 30 days, and many required a relatively prolonged maturation phase, the presence of glia, and additional stressor conditions in order to yield a disease phenotype.…”
Section: Single-cell Analysis Enables Attribution Of Early and Convermentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that TDP-43 naturally de-mixes in the nucleus, and shuttles to the cytoplasm in response to multiple stresses (21). Loss of nuclear TDP-43 causes usage of cryptic splice (22)(23)(24) and polyadenylation sites (24), dysregulating many important neuronal genes such as HDAC6 (25) and stathmin-2 (22,24).…”
Section: Mislocalization and Aggregation Of The Heterogeneous Nuclearmentioning
confidence: 99%